THE IMPLEMENTATION OF COLLABORATIVE STRATEGY IN TEACHING STUDENTS’ READING COMPREHENSION AT SMP NEGERI 2 ERIS - Risaldi Mose; Nitha V. F. Liando; Trully Wungow (Program Studi Pendidikan Bahasa Inggris, 2022)
This study aimed to determine students' reading comprehension ability in narrative text by using Collaborative Strategic Reading (CSR) as a strategy in learning at students of SMP Negeri 2 Eris. The research approach used in this study is a quantitative method using pre-Experimental design and for the sample of this research, namely the eighth-grade students of SMP Negeri 2 Eris, consisting of 18 students. For the research instrument, the writer used 4 reading texts with 20 questions in it and the writer divided the meeting into 3 meetings to taught the students. All the data that collected taken from the test that is pretest results is 51 and the posttest is 86. The students score achievement from pretest to posttest is 35. The results of this study show that the implementation of collaborative strategy reading can improve student reading comprehension in narrative text and this strategy can be a solution for lack of students’ reading comprehension.